miR-1306 induces cell apoptosis by targeting BMPR1B gene in the ovine granulosa cells - Abdurahman, Anwar; Aierken, Wusimanjiang; Zhang, Fei; Obulkasim, Rahmantay; Aniwashi, Jueken; Sulayman, Ablat (Frontiers in Genetics, 2022)
Bone morphogenetic protein receptor type-1B (BMPR1B) is one of the major gene for sheep prolificacy. However, few studies investigated its regulatory region. In this study, we reported that miR-1306 is a direct inhibitor of BMPR1B gene in the ovine granulosa cells (ovine GCs). We detected a miRNA response element of miR-1306 in the 3’ untranslated region of the ovine BMPR1B gene. Luciferase assay showed that the ovine BMPR1B gene is a direct target of miR-1306. qPCR and western blotting revealed that miR-1306 reduces the expression of BMPR1B mRNA and protein in the ovine granulosa cells. Furthermore, miR-1306 promoted cell apoptosis by suppressing BMPR1B expression in the ovine granulosa cells. Overall, our results suggest that miR-1306 is an epigenetic regulator of BMPR1B, and may serve as a potential target to improve the fecundity of sheep.